Research on Monitoring Methods for Electrostatic Discharge Pulses in Spacecraft Dielectric Materials - Hong Yin; Cunhui Li; Chengxuan Zhao; Xiaogang Qin; Xiaojin Lu; Xuan Wen; Liang Shi; Qing Liu; Jun Wang; Hanwu Jia; Shengsheng Yang (Micromachines)
Space particle radiation induces charging and discharging phenomena in spacecraft dielectric materials, leading to electrostatic discharge (ESD) and electromagnetic pulses (EMP), which pose significant risks to spacecraft electronic systems by causing interference and potential damage. Accurate and timely monitoring of these phenomena, combined with a comprehensive understanding of their underlying mechanisms, is critical for developing effective protection strategies against satellite charging effects. Addressing in-orbit monitoring requirements, this study proposes the design of a compact sleeve monopole antenna. Through simulations, the relationships between the antenna’s design parameters and its voltage standing wave ratio (VSWR) are analyzed alongside its critical performance characteristics, including frequency band, gain, radiation pattern, and matching circuit. The proposed antenna demonstrates operation within a frequency range of (28.73–31.25) MHz (VSWR < 2), with a center frequency of 30 MHz and a relative bandwidth of 8.4%. Performance evaluations and simulation-based experiments reveal that the antenna can measure pulse signals with electric field strengths ranging from (−1000 to −80) V/m and (80 to 1000) V/m, centered at 25.47 MHz. It reliably monitors discharge pulses generated by electron irradiation on spacecraft-grade FR4 (Flame-Retardant 4) dielectric materials, providing technical support for the engineering application of discharge research in space environments.